Long axial field of view PET/CT in critically ill patients: lessons from a case report - J. H. van Snick; B. van Leer; B. van Leer; M. W. N. Nijsten; J. Pillay; J. Pillay; R. H. J. A. Slart; R. H. J. A. Slart; A. W. J. M. Glaudemans; N. D. van Rijsewijk (Frontiers in Medicine, 2024)
The introduction of new long axial field of view (LAFOV) scanners is a major milestone in positron emission tomography/computed tomography (PET/CT) imaging. With these new systems a revolutionary reduction in scan time can be achieved, concurrently lowering tracer dose. Therefore, PET/CT has come within reach for groups of patients in whom PET/CT previously was undesirable. In this case report we discuss the procedure of a continuous bed motion (CBM) total-body [18F]FDG PET/CT scan in an intensive care patient. We emphasize the clinical and technical possibilities with this new camera system, a matched clinical protocol, and the added value of a dedicated team.